1997
DOI: 10.1021/ja970639b
|View full text |Cite
|
Sign up to set email alerts
|

Group 5 Metallocene Complexes as Models for Metal-Mediated Hydroboration:  Synthesis of a Reactive Borane Adduct, endo-Cp*2Nb(H2BO2C6H4), via Hydroboration of Coordinated Olefins

Abstract: The olefin complexes Cp*2M(CH2CH(R))(H) (R = H (1), CH3 (2); M = Nb (a), Ta (b)) react cleanly with catecholborane (HBCat) and HBO2C6H3-4- t Bu (HBCat‘) to give Cp*2M(H2BCat) (M = Nb (5a), Ta (5b)) and Cp*2M(H2BCat‘) (M = Nb (6a), Ta (6b)) and the anti-Markovnikov hydroboration products CatBCH2CH2R and Cat‘BCH2CH2R. Compounds 2a and 2b react with DBCat‘ (DBO2C6H3-4- t Bu) to afford the deuterated analogs Cp*2M(D2BCat‘) (M = Nb (6a), Ta (6b)) where the deuterium label is incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 59 publications
2
34
0
1
Order By: Relevance
“…Garcia and coworker have recently reported the r-borane complexes of nickel(0) [10]. Synthesis and bonding of the transition metal complexes containing residual BÁ Á ÁH interaction have been reported [11][12][13][14][15][16][17][18]. Mechanistic studies have revealed that r-borane complexes can be intermediates in catalytic hydroboration and borylation reactions [13,[19][20][21].…”
mentioning
confidence: 99%
“…Garcia and coworker have recently reported the r-borane complexes of nickel(0) [10]. Synthesis and bonding of the transition metal complexes containing residual BÁ Á ÁH interaction have been reported [11][12][13][14][15][16][17][18]. Mechanistic studies have revealed that r-borane complexes can be intermediates in catalytic hydroboration and borylation reactions [13,[19][20][21].…”
mentioning
confidence: 99%
“…The average bridging NbeSe distance (2.6992 Å) in 2 is about 0.06 Å longer than that observed in [Nb 2 Se 4 (Et 2 NCS 2 ) 4 ] (2.6392 Å) [24]. The average NbeB distance of 2.386 Å lies in the range of those reported for the niobium boron complexes [25]. The angle between the wings of the Nb 2 B 2 "butterfly" of 163.74 is comparable to the related cluster [(Cp * Mo) 2 B 4 H 8 (m-Seph)] [13].…”
Section: Resultsmentioning
confidence: 54%
“…The proposed mechanism for the metallocene complexes of Group 5 metals and lanthanides involves the coordination of alkene to the metal hydride (51), followed [67]. The product will be then provided via the direct σ-bond metathesis between HBcat and 53 or an oxidative addition/reductive elimination sequence (53 → 54 → 51).…”
Section: Catalytic Cyclesmentioning
confidence: 99%
“…The product will be then provided via the direct σ-bond metathesis between HBcat and 53 or an oxidative addition/reductive elimination sequence (53 → 54 → 51). These processes are studied in detail for the Group 5 metals such as Nb and Ta [67][68][69]; however, an ab initio calculation [70] for the hydroboration of C 2 H 4 with HB(OH) 2 supports an analogous cycle for the Cp 2 Sm catalyst. Due to the high oxophilicity of the samarium atom, the last σ-bond metathesis (53 → 51) yields an acid/base complex between EtB(OH) 2 and Cp 2 SmH.…”
Section: Catalytic Cyclesmentioning
confidence: 99%
See 1 more Smart Citation